Finite elements study of the Flexi Post and Flexi Flange post systems in a maxillary central incisor (Pesquisa Odontológica Brasileira, 2003)
The use of post and core systems has become an excellent alternative for restoring endodontically treated teeth. The aim of this study was to evaluate the von Mises, maximal compressive and tensile stresses distribution using the Finite Element Method (FEM) on human teeth restored with different post and core systems. The analysis was made on endodontically treated maxillary central incisors. The post systems used in this investigation were the stainless steel or titanium Flexi Post/Flexi Flange. Composite resin was used as core material and resin cement was the cement material of choice to seat a full porcelain crown. The bi-dimensional mathematical model was created from pictures taken from an intact human maxillary central incisor and prefabricated posts. This image was transferred to a personal computer in the MSC/Nastran 4.5 software. A static and linear analysis treatment was performed when a 45º load of 100 N was applied on the lingual surface of the tooth. Based on the results obtained, it can be concluded that the post design and its material can alter the stress pattern distribution.